Plan Quality and Treatment Efficiency for Radiosurgery to Multiple Brain Metastases: Non-Coplanar RapidArc vs. Gamma Knife - Liu, Haisong; Andrews, David W.; Evans, James J.; Werner-Wasik, Maria; Yu, Yan; Dicker, Adam Paul; Shi, Wenyin (Frontiers in Oncology, 2016)
Objectives: This study compares the dosimetry and efficiency of two modern radiosurgery (SRS) modalities for multiple brain metastases (Gamma Knife and LINAC-based RapidArc/volumetric modulated arc therapy), with a special focus on the comparison of low dose spread. Methods: Six patients with three or four small brain metastases were used in this study. The size of targets varied from 0.1 ~ 10.5 cc. SRS doses were prescribed according to size of lesions. SRS plans were made using both Gamma Knife® Perfexion and a single-isocenter, multiple non-coplanar RapidArc®. Dosimetric parameters analyzed included RTOG conformity index (CI), gradient index (GI), 12 Gy isodose volume (V12Gy) for each target, and the dose “spread” (Dspread) for each plan. Dspread reflects SRS plan’s capability of confining radiation to within the local vicinity of the lesion and to not spread out to the surrounding normal brain tissues. Each plan has a dose (Dspread), such that once dose decreases below Dspread (on total tissue DVH), isodose volume starts increasing dramatically. Dspread is defined as that dose when volume increase first exceeds 20 cc per 0.1 Gy dose decrease. Results: RapidArc SRS has smaller CI (1.19 ±0.14 vs. 1.50 ± 0.16, p<0.001) and larger GI (4.77 ± 1.49 vs. 3.65 ± 0.98, p <0.01). V12Gy results were comparable (2.73 ± 1.38 cc vs. 3.06 ± 2.20 cc, p = 0.58). Moderate to lower dose spread, V6, V4.5, and V3, were also equivalent. Gamma Knife plans achieved better very low dose spread (≤3 Gy) and also had slightly smaller Dspread, 1.9 Gy vs 2.5 Gy. Total treatment time for Gamma Knife is estimated between 60~100 min. Gamma Knife treatments are between 3~5 times longer compared to RapidArc treatment techniques. Conclusion: Dosimetric parameters reflecting prescription dose conformality (CI), dose fall off (GI), radiation necrosis indicator (V12Gy), and dose spread (Dspread) were compared between Gamma Knife SRS and RapidArc SRS for multi-mets. RapidArc plans have smaller CI but larger GI. V12Gy are comparable. Gamma Knife appears better at reducing only very low dose spread (<3Gy). The treatment time of RapidArc SRS is significantly reduced compared to Gamma Knife SRS.